Application of maqasid al-shari'ah in Indonesian liberal Muslim thought on marriage and divorce - Abdul Aziz, Muhammad (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research examines the extent of the application of the so-called maqaṣid al-shari'ah offered by Indonesian liberal Muslims. The examination is interesting given that the maqaṣid al-shari'ah itself is a contested concept between classical and liberal Muslim scholars. The appraisal that is focused on marriage and divorce issues is also crucial because of the influence of feminists who are inseparable supporters of the liberals and the dispute caused has also divided the society in such a way that a winning solution is necessary. The data collection employed two important means, namely library-based resources which mainly relate to the maqaṣid al-shari'ah, liberalism, and women's issues, and the interview of two prominent and representative Indonesian liberal figures by which the researcher sought to confirm 'deviant' activities that are commonly associated with them. Analysing Muslim family issues raised by the liberals that range from guardianship, polygamy, interreligious and same-sex marriage, divorce (ṭalaq) and waiting period ('iddah), the research reveals a number of typical features of their application. The liberals' maqaṣid turns out to be anthropomorphic, that is reflected in some key concepts such as definition (ta'rif), establishment (ithbat) and classification (taqsim). They also do not incorporate the leading scholars' views comprehensively which eventually leads their maqaṣid being relatively partial. Such partiality in turn leads to the overgeneralization of the maqaṣid concept where some theoretical implications are not included. Additionally, the liberals' understanding of the concept in question appears relative which changes too easily over time. No less importantly, the research's interview confirms that liberal categorization should be based on ideas provoked, not individuality as what has happened in some cases in Indonesia. In short, such findings denote the deviation of the Indonesian liberals in the process of application from that of the classical mainstream.